Respon Pertumbuhandan ProduksiTanaman Jagung Manis (Zea maysvar.saccharataSturt.) Terhadap Pemberian Abu Janjang Kelapa SawitdanPupuk N - Firdaus, David; Adiwirman, Adiwirman; Dini, Isna Rahma (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2018)
The aim of this study was to determine the effect of palm oil fruit bunch ash, N fertilizer and interaction between palm oil fruit bunch ash and Nfertilizer on the growth and yieldÂ of sweet corn. The research was carried out in the experiment station and the Plant Ecofisilogy Laboratory of the Faculty of Agriculture, University of Riau. This study used factorial randomized block design (RBD) consisting of two factors and 3 replications. The first factor was palm oil fruit bunch ash which consists of four levels: K0: 0 t.ha-1, K1: 1.5 t.ha-1 (0.9 kg. 6m-2), K2: 2 t.ha-1 (1.2 kg. 6m-2), K3: 2.5 t.ha-1 (1.5 kg. 6m-2). The second factor was N fertilizer which consists of two levels, namely: P1: N 115 kg.ha-1 (69 g. 6m-2) P2: Urea 138 kg. Ha-1 (82.8 g. 6m-2). The results showed that the increase in palm oil fruit bunch ash increased the plant height, number of leaves, and number of cobs harvested. Increasing the N dose only increases plant height. The interaction of palm oil bins and N fertilizers only increases plant height.Keywords: Sweet corn, palm oil bare ash, N fertilizer